Regulations on Recidivism in Corruption Crimes and Their Implications for the System of Aggravated Sentencing - Elinda Novita Dewi; Ali Masyhar Mursyid; Cahya Wulandari (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Regulations regarding recidivism in corruption offenses are a key aspect of the system of aggravated penalties, which aims to deter repeat offenders. However, Indonesian positive law still faces normative challenges regarding the regulation of recidivism in corruption offenses. This study aims to analyze the issues surrounding the regulation of recidivism in corruption crimes from the perspective of criminal law policy and its implications for the system of aggravated penalties. This study employs a normative legal research method with a qualitative approach, utilizing both a legislative and a conceptual framework. The findings indicate that Law No. 31 of 1999 as amended by Law No. 20 of 2001 does not explicitly regulate the concept, requirements, and mechanisms for applying recidivism. This situation creates a legal vacuum that leads to legal uncertainty, potential conflicts of law, and disparities in sentencing within the judicial system. Furthermore, the regulations on corruption were last updated in 2001, meaning that, in substance, they have been in effect for more than two decades without significant changes, even though social and economic dynamics and the methods of corruption continue to evolve. This situation has the potential to create various legal loopholes that can be exploited to commit acts of corruption. Therefore, it is necessary to explicitly reformulate the recidivism provisions in the Law on the Eradication of Corruption in order to strengthen the system of aggravated penalties and enhance the effectiveness of anti-corruption policies.